Homeopathy and National-Socialism - Fortes, Lore (Circumscribere International Journal for the History of Science, 2010)
It is a well known, yet still polemical issue the support homeopathy received from the Nazi regime. As a fact, National Socialism favored so-called natural therapies as a whole, as well as their integration with conventional medicine into one single approach known as Neue Deutsche Heilkunde (New German Medicine). The latter has come under the attention of scholars very recently, however the specific role of homeopathy has only been very sparsely address. It is difficult to trace the particular paths of homeopathy at that time, since, on the one hand, it was intertwined with the other types of alternative medicine included in the project of the New German Medicine, and on the other, it shared the agenda of conventional medicine against lay practice. This article aims at discussing expressions particular to homeopaths as appearing in journals of the National Socialist period.